Mathematical Problems Solving Conception (MaProSC) Scale - E. Catindoy, Dulce (International Journal of English Literature and Social Sciences (IJELS), 2021)
The problem of the current research is to develop and instrument that will assess students’ conception on mathematical problem solving as a process and as to its characteristics as an activity in a classroom setting. A confirmatory factor analysis with Varimax rotation and elimination loadings were used in the validation of the pre-identified constructs which are problem solving as a process and problem solving as to its characteristics. There were 19-items retained in the first factor about students’ views on problem solving as a process and 17 items describing on students’ perception of mathematical problem solving as to its characteristics. The results of this study also need to be re-examined to determine if they can be replicated with other samples of students as well as adding factors and items that would measure students’ conception on mathematical problem solving.